2014
DOI: 10.1186/1471-230x-14-113
|View full text |Cite
|
Sign up to set email alerts
|

Association of MRC-1 and IL-28Bwith the treatment outcome of hepatitis C: a case control study

Abstract: BackgroundThe aim of this study was to evaluate whether polymorphisms of the mannose receptor C type 1 (MRC-1) and interleukin 28B (IL-28B) genes are associated with the treatment outcome of patients infected with hepatitis C virus genotypes 1 and 2 (HCV-1 and HCV-2, respectively) who are treated with peginterferon plus ribavirin (PEG-IFNα-RBV).MethodsWe analyzed the association of the patients’ sustained viral responses (SVRs) to PEG-IFNα-RBV therapy with 2 single nucleotide polymorphisms (SNPs) in MRC-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…These results are consistent with other studies, which presented similar results [29,36]. On the other hand, several studies reported mean HCV RNA level had a significantly higher in the carriers of rs8099917 G allele and the non-SVR group [22,27,32,35,40].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with other studies, which presented similar results [29,36]. On the other hand, several studies reported mean HCV RNA level had a significantly higher in the carriers of rs8099917 G allele and the non-SVR group [22,27,32,35,40].…”
Section: Discussionsupporting
confidence: 92%
“…According to the previous results, the frequencies of T and G allele of rs8099917 polymorphism among the populations are distributed as 73.2% and 26.8% in Australian, 82% and 12% in Japanese, 81.8% and 18.2% in Slovakian, 70.2% and 29.8% in Brazilian, 92.3% and 7.7% in Chinese, respectively [4,22,28,34,35]. Moreover, in a multicenter study from Europe, Caucasian patients' allele frequencies were in 79% T allele and in 21% G allele [32].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…AST levels are used for the diagnosis of various liver diseases like hepatitis and cirrhosis. In a recent study variants in MRC1 were reported to be associated with treatment outcomes for hepatitis C 24 .…”
Section: Resultsmentioning
confidence: 99%
“…MRC1 (mannose receptor, C type 1), a scavenger receptor mainly expressed in the membrane of macrophages, assists macrophages in recognizing and binding the high-mannose structures of potentially pathogenic viruses and bacteria, mediating the endocytosis and causing immune response [23]. Moreover, FPR1 (formyl peptide receptor 1) which belongs to the family of formyl peptide receptors can be activated by N-formyl peptides [24].…”
Section: Discussionmentioning
confidence: 99%